Penerapan Model Problem Based Learning dalam Membentuk Kemampuan Pemecahan Masalah pada Siswa di Era Digital - Wafik Andini; Reina Dewi Masitoh; Siska Puspitarani; Jadiaman Parhusip (Journal on Education, 2025)
This study aims to explore the implementation of the Problem Based Learning (PBL) model in developing students' problem-solving skills in the digital era. The data collected is found in two cycles. After the data is collected then the data is analyzed descriptively. The results of the study indicate that the gradual implementation of PBL significantly improves students' problem-solving skills. In cycle 1, students began to understand the stages of PBL but faced challenges in group collaboration and managing information from digital sources. After improvements were made in cycle 2, such as training in the use of digital technology and strengthening analytical strategies, students showed significant progress in formulating creative, systematic, and data-driven solutions. Moreover, the integration of digital technology in the learning process proved effective in supporting information exploration and presenting solutions engagingly. This study concludes that PBL, supported by digital technology, is a relevant learning strategy for developing critical thinking, collaborative, and innovative skills in students in the digital era. Recommendations are provided for teachers to continue developing their competencies in integrating PBL and technology into their teaching to enhance the quality of education.